Association of polymorphisms in STRA6 gene with gestational diabetes mellitus in a Chinese Han population. Issue 11 (March 2019) - Hu, Shimin; Yan, Junxia; You, Yiping; Yang, Guilian; Zhou, Hui; Li, Xun; Liao, Xin; Tan, Hongzhuan
Abstract : Abstract: Cell and animal experiments have found that in addition to being a retinol transporter, Stimulated by Retinoic Acid 6 (STRA6) also functions as a surface signaling receptor by which retinol regulates insulin responses. Several studies revealed that the STRA6 gene may contribute to the pathogenesis of type 2 diabetes mellitus (T2DM). Gestational diabetes mellitus (GDM) and T2DM have some risk factors in common. The present study was directed to investigate whether the 3 single nucleotide polymorphism (SNPs) (rs11633768, rs351219, and rs736118) of STRA6 correlate with the development of GDM in Chinese pregnant women. We also aimed to estimate the relationship between SNPs with fasting blood glucose level, 1-hour and 2-hour blood glucose levels after 75 g oral glucose intake, fasting insulin and insulin resistance levels to better study the relationship between STRA6 and glucose metabolism. Case–control studies were conducted to compare the GDM and control groups. A total of 334 cases and 367 controls were recruited. Three tagSNPs of STRA6, rs11633768, rs351219, and rs736118, were selected. A chi-square test, logistic regression, and linear regression were used to estimate the relationship between SNPs with GDM risk and oral glucose tolerance test (OGTT), fasting insulin and homeostasis model assessment of insulin resistance (HOMA-IR) levels. Regression analyses were all adjusted by maternal age, pre-pregnancy BMI, and weekly BMI growth. The Bonferroni correction was applied for multiple comparisons. After adjusting the maternal age, pre-pregnancy BMI and weekly BMI growth, STRA6 rs736118 was associated with fasting insulin level (Beta = −1.468, P = .036), and the association between rs736118 and HOMA-IR was of borderline significance (Beta = −0.290, P = .093) under the dominance model. This study found that there is a significant association between STRA6 polymorphism and GDM.